2013
DOI: 10.23986/afsci.6698
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three silage inoculants on aerobic stability in grass, clover-grass, lucerne and maize silages

Abstract: The objective of the study was to investigate the effects of homofermentative and heterofermentative lactic acid bacteria (LAB) inoculants on fermentation and aerobic stability in a variety of crops and dry matter concentrations. The experiments were conducted with lucerne, ryegrass, ryegrass-timothy, red clover-ryegrass and whole crop maize using three additives in laboratory scale conditions. Each treatment and crop was replicated five times when determining the chemical composition and aerobic stability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The DM content of forage and silage, chemical composition, volatile fatty acids, lactic acid and alcohols concentrations were determined as described previously by Jatkauskas et al (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DM content of forage and silage, chemical composition, volatile fatty acids, lactic acid and alcohols concentrations were determined as described previously by Jatkauskas et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…Kleinschmitt et al (2005) indicated that improved aerobic stability was observed in different types of forages when acetic acid and propionic acid production in silage fermentation increased with L. buchneri inoculation. In the study (Jatkauskas et al, 2013), selected LAB inoculants were efficient in improving fermentation, reducing protein breakdown and nutrient losses of grass, clover-grass, lucerne and maize silages. Homofermentative LAB in combination with sodium benzoate led to silages with higher lactic acid content, when inoculation with single heterofermentative LAB or with mixture of homo-and heterofermentative LAB resulted in higher levels of acetic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Silage treatments with homofermentative and heterofermentative lactobacilli can achieve considerably better aerobic stability. Additive application of lactobacilli species decreases pH, as well as levels of butyric acid, alcohol and ammonium [16]. The aim of the present study was to determine the influence of two types of treatment (biological and chemical) on the occurrence of biogenic amines, nutrient value, and hygienic quality of lucerne silages.…”
Section: Microbiologymentioning
confidence: 99%
“…The inoculant had lower concentrations of ammonia-N and alfalfa silage pH and no 3-hydroxybutyric acid was detected in any of the silages (ContrerasGovea et al, 2013). Jatkauskas et al (2013) reported that homofermentative and heterofermentative lactic acid bacteria inoculants (L. buchneri, L. buchneri in combination with Enterococcus faecium and L. plantarum, E. faecium in combination with L. plantarum and Lactococcus lactis) were able to reduce pH, formation of butyric acid, alcohols and ammonia-N in grass, clovergrass, alfalfa, and maize silages. It was observed that the aerobic stability of silages was improved (P < 0.05) (Jatkauskas et al, 2013).…”
Section: Alfalfa Before Ensilingmentioning
confidence: 99%
“…Jatkauskas et al (2013) reported that homofermentative and heterofermentative lactic acid bacteria inoculants (L. buchneri, L. buchneri in combination with Enterococcus faecium and L. plantarum, E. faecium in combination with L. plantarum and Lactococcus lactis) were able to reduce pH, formation of butyric acid, alcohols and ammonia-N in grass, clovergrass, alfalfa, and maize silages. It was observed that the aerobic stability of silages was improved (P < 0.05) (Jatkauskas et al, 2013). Ohshima et al (1997) presented the improvement of alfalfa silage quality by the addition of L. casei at 20 °C, but the more effective additive was shown to be previously fermented juice.…”
Section: Alfalfa Before Ensilingmentioning
confidence: 99%